Seroprevalence of neospora caninum in dairy cattle in Sama Grande district of Sama-Inclán, Tacna - Víctor Vélez (2019)
A study was designed to determine the seroprevalence of N. caninum in dairy cattle in the area of Grande Sama Sama -Inclan District , Province and Department of Tacna. Blood samples from 115 dairy cattle distributed by age ( 2 to 4.5 , <4.5 to 7 and < 7-10 years) and place of origin ( Arequipa. Ite , Sama and Yarada ). By immunofluorescence test was determined seroprevalence N. caninum , which turned out to be moderate with a value of 28.70 ± 8.27 , considering the age of the animals was observed that animals of< 7-lO years had the highest values of seroprevalence (44.44 ± 32 , 46 ) , then the animals of 2 to 4.5 years ( 27.87 ± 11.25 ) , and finally the animals of < 4.5 to 7 years ( 26.67 ± 12.92 ) , respectively. On the other hand , the seroprevalence of the parasite into consideration the place of origin was 30.00 ± 16.40 for animals from Arequipa, 50.00 ± 40. 01 for Ite , 30.00 ± 10.74, for Sama, and absent for Yarada respectively. Analyzing The age and origin of the animals as possible risk factors, these were not statistically significant. It is also likely that other risk factors would condition the presence of the parasite in the study area.